2010
DOI: 10.2337/dc09-1959
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adjunctive Exenatide Therapy in Pediatric Type 1 Diabetes

Abstract: OBJECTIVEExenatide improves postprandial glycemic excursions in type 2 diabetes. Exenatide could benefit type 1 diabetes as well. We aimed to determine an effective and safe glucose-lowering adjuvant exenatide dose in adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODSEight subjects completed a three-part double-blinded randomized controlled study of premeal exenatide. Two doses of exenatide (1.25 and 2.5 μg) were compared with insulin monotherapy. Prandial insulin dose was reduced by 20%. Gastric emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 14 publications
(11 reference statements)
5
52
1
4
Order By: Relevance
“…3,24,25 This results in a very complicated treatment algorithm especially if using multiple-hormonal therapy in CL. 25 Hence, our research has focused on studying newer analogs such as exenatide 9,10 (twice daily) and now liraglutide (once daily), to improve postprandial glucose concentrations in type 1 diabetes, thus reducing treatment complexity. As improved treatment options emerge, efficacy in CL must be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,24,25 This results in a very complicated treatment algorithm especially if using multiple-hormonal therapy in CL. 25 Hence, our research has focused on studying newer analogs such as exenatide 9,10 (twice daily) and now liraglutide (once daily), to improve postprandial glucose concentrations in type 1 diabetes, thus reducing treatment complexity. As improved treatment options emerge, efficacy in CL must be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a power of .8, alpha of .05, correlation coefficient of r = .5, 9 and Figure 1. Design of the study evaluating overnight and daytime closed-loop delivery.…”
Section: Study Bmentioning
confidence: 99%
See 1 more Smart Citation
“…pokazują, że natywny GLP-1 zmniejsza hiperglikemię poposił-kową również w cukrzycy typu 1, prawdopodobnie przez wpływ na supresję glukagonu. Podobny efekt zaobserwowano po iniekcjach eksanatydu u młodych pacjentów z cukrzycą typu 2 [23]. W badaniach z zastosowaniem liraglutydu udało się także wykazać jego korzystny wpływ na kontrolę glikemii poposiłkowej.…”
Section: Leki Z Grupy Inkretyn W Terapii Cukrzycy Typuunclassified
“…[44][45][46] Varanasi et al showed that the administration of a GLP-1 analogue in individuals with well controlled type 1 diabetes mellitus improved mean fasting glucose and decreased glycaemic excursions. These improvements in glycaemic control were evident after one week of treatment and persisted for the 24-week trial.…”
Section: Currently Available Drugs That Target Alpha Cell Functionmentioning
confidence: 99%